Emergence and spread patterns of antibiotic resistance genes during two different aerobic granular sludge cultivation processes. (April 2020) - Li, Ding-Chang; Gao, Jing-Feng; Zhang, Shu-Jun; Gao, Yong-Qing; Sun, Li-Xin
Graphical abstract: Highlights: Traditional AGS (T-AGS) process had lower average relative abundances of ARGs. Enhanced AGS (E-AGS) process had weaker ability of ARGs enrichment than T-AGS. E-AGS process had more potential hosts harboring ARGs than T-AGS process. TnpA and intI1 were the main MGEs during T-AGS and E-AGS processes, respectively. Distinct co-occurrence patterns between ARGs and bacterial community were detected. Abstract: The prevalence and accumulation of antibiotic resistance genes (ARGs) were frequently detected in biological wastewater treatment processes, which might cause potential health crisis to human. In present study, the fates of ARGs during two different aerobic granular sludge (AGS) cultivation processes were investigated. The results showed that traditional AGS (T-AGS) cultivation process and enhanced AGS (E-AGS) cultivation process had significant differences ( P < 0.005) in ARGs shift patterns. E-AGS process had higher average relative abundance (0.280 ± 0.079) of ARGs than T-AGS process (0.130 ± 0.041), while the intensity of ARGs enrichment during E-AGS (1.52–5.29 fold) was lower than T-AGS (3.79–75.31 fold) process. TnpA and intI1 as two different types of mobile genetic elements (MGEs) carrying ARGs, were observed to contribute significantly to the horizontal gene transfer (HGT) during T-AGS (r = 0.902, P < 0.050) and E-AGS (r = 0.823, P < 0.001) processes, respectively. Higher HGT level took place and more possible potential hosts (25 hosts) harboring ARGs were detected during E-AGS process comparing with T-AGS process (17 hosts). Meanwhile, over large AGS might increase the propagation of several antibiotic deactivation ARGs, so it was not advised. Overall, whether during T-AGS or during E-AGS process which was applied in a pilot-scale sequencing batch reactor treating municipal wastewater, the accumulation and spread of ARGs were inevitable. It should be valued that some suitable pre-treatments of seed sludge should be executed, meanwhile, advanced treatment for removing of ARGs in AGS should be conducted to maintain the relative abundances of ARGs at relatively low level.